An investigative case study of the introduction of democratic decision-making within an East London secondary school - Carelse, Garth Craig (Rhodes University, Faculty of Education, Department of Education, 2000)
The move towards greater democracy and participation in our education system is legislated quite succinctly in our South African Schools Act. The Act furthermore, and more importantly for this case study, posits that decision-making should be democratic in nature and our schools should eventually become governed in a collaborative and co-operative manner. Other policy texts such as the Labour Relations Act and the South African Constitution canonise the demand for a democratic South African society. This study investigates how democratic decision-making practices are taking place in an East London Secondary School namely Ebenezer Majombozi High. Even though distinct links exist between management and governance arms of schools, this study concentrates predominantly on decision-making within the school governing body and touches briefly on management thinking trends as a theoretical background to the kind of management at the school. What makes the school interesting as a case study is its rich history and its location in a deprived and impoverished township environment. The school was also part of the ex-Department of Education and Training, the black educational department of the past apartheid state. The kind of research undertaken was in the form of unstructured personal interviews with influential stakeholders at the school. Some of these stakeholders fonn part of the school governing body and the questions asked probed forms of governance at the school and how decision-making impacted on the overall school governance. The research findings acknowledges that decision-making does occur democratically at the school but that the practical implementation of positive consensual decisions are rarely realized. The school governing body only meets to deal with crises underpinned by a lack of learning and teaching and has not even debated the policies within the South African Schools Act. The study also argues that only by building capacity within the school and empowering the stakeholders, can constructive participation by all become a reality.
Keywords: School management and organization -- South Africa; Decision making -- Cast studies; Education and state; Ebenezer Majombozi High